Alcoholism – neuro-pathophysiology, health promotion challenges - Gogichadze, Mariam; Landia, Natia (Caucasus Journal of Health Sciences and Public Health, 2019)
Ethanol (ET), together with caffeine and nicotine is extensively used trough the world. It is documented that as many as 80% of men and 60% of women in developed countries drink at some time during their lives. The dangerous and destructive use of alcohol is a fundamental pivotal factor to death, disease and injury. Although its anxiolytic, euphoric, analgesic and in some cases antidepressant effects must be foreseen, and it is for this reason that people begin to consume of alcohol that leads to abuse and alcoholism at last. In the submitted review paper some aspects of ET effects on the neurotransmitter systems and correlated behavior alternation are discussed. The effectiveness of the methods used in experimental conditions is specifically discussed.